Occupational Stress and Coping Mechanisms Among Senior Uniformed Personnel in Philippine National Police - Olivar, Lourdelyn S.; Valera, Maria Alicia B.; Ocampo, Danilo L.; de Torres, Mhel Jeric R.; Gonzales, Reena Jane E.; Yabut, Geralyn C.; Villa, Elizabeth B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aimed to assess the occupational stress and coping mechanisms among senior uniformed personnel in the Philippine National Police. This study employed the use of descriptive correlational research design utilizing survey methodology. Research locale was limited to Laguna. The respondents were the 100 senior uniformed personnel in the locale of the study and were selected using random sampling technique. The research instrument in this study was a survey questionnaire adopted from Juczyński & Ogińska-Bulik (2022). Data were analyzed using percentage, mean, rank order and Pearson-r. The study found that those who used adaptive coping strategies had lower levels of stress than those who used maladaptive strategies. The results also showed that those who used adaptive strategies had better mental health outcomes. Individuals who employed adaptive coping strategies experienced lower levels of stress compared to those who used maladaptive strategies. This highlights the importance of cultivating effective coping mechanisms to mitigate stress. The study indicates that the choice of coping strategies has a notable impact on mental health outcomes. Those who employed adaptive strategies reported better mental health, suggesting that the way individuals cope with stressors can have lasting effects on their overall psychological well-being. The findings support the promotion of adaptive coping mechanisms to enhance stress resilience. This could involve educational programs, workshops, or interventions aimed at equipping individuals with effective strategies to cope with stressors in healthier ways.